2018
DOI: 10.1371/journal.pone.0204866
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic, nuclear, and total PBK/TOPK expression is associated with prognosis in colorectal cancer patients: A retrospective analysis based on immunohistochemistry stain of tissue microarrays

Abstract: ObjectivePDZ-binding kinase/T-LAK cell-originated protein kinase (PBK/TOPK) regulates components of the cell cycle, including cell growth, immune responses, DNA damage repair, apoptosis, and inflammation. PBK/TOPK may also accelerate tumorigenesis in colorectal cancer.MethodsWe investigated the impact of PBK/TOPK on the clinical outcome of colorectal cancer patients to further identify its role in colorectal cancer. PBK/TOPK immunoreactivity was analyzed by immunohistochemistry in 162 cancer specimens from pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…Though our data are in peripheral blood and it is unclear whether decreased CD8-T lymphocyte proportions are specifically a consequence of LINE-1 hypomethylation, in an analysis of 21 tumor types with nearly 7000 samples, reduced repeat element methylation was associated with reduced infiltration of CD8-T lymphocytes [ 47 ]. LINE-1 hypomethylation and activation have been associated with autoimmune diseases [ 49 51 ], further affirming the observed hypomethylation and reduction in CD8-T cell proportions.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Though our data are in peripheral blood and it is unclear whether decreased CD8-T lymphocyte proportions are specifically a consequence of LINE-1 hypomethylation, in an analysis of 21 tumor types with nearly 7000 samples, reduced repeat element methylation was associated with reduced infiltration of CD8-T lymphocytes [ 47 ]. LINE-1 hypomethylation and activation have been associated with autoimmune diseases [ 49 51 ], further affirming the observed hypomethylation and reduction in CD8-T cell proportions.…”
Section: Discussionsupporting
confidence: 53%
“…Of these, several stand out given previous studies. PDZ binding-kinase ( PBK ) (also named T-lymphokine-activated killer cell-originated protein kinase ( TOPK )) has wide-ranging regulation, including cell growth and immune function [ 48 , 49 ]. Solute Carrier Organic Anion Transporter Family Member 1A2 ( SLCO1A2 ) has been implicated in transporting sulfated steroids across the blood–brain barrier [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“… 89 PDZ-binding kinase (encoded by PBK ) can regulate cell cycle processes. 90 Although PBK is barely detectable in normal somatic tissues, it is often elevated in various tumor tissues and is therefore an important target for cancer screening and targeted therapy. 91 , 92 Recent research has shown that PBK overexpression promotes migration and invasion of HCC, and it could be a therapeutic target for HCC metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…PDZ-binding kinase (PBK) promotes malignant tumor progression in various cancers such as colorectal and oral cancer. Su et al found that PBK/TOPK expression detected by the immunohistochemical staining was signi cantly associated with prognosis in colorectal cancer patients based on a retrospective analysis [10]. Chang et al found that PBK was highly expressed in oral cancer patients, and that high PBK/TOPK expression could be a favorable prognosis marker for these patients [11].…”
Section: Discussionmentioning
confidence: 99%